Detekce a výskyt mutací genu BRCA 1 u pacientek s karcinomem prsu a ovaria - Jancárková, N; Zikán, M; Pohlreich, P; Freitag, P; Matous, B; Zivný, J (Ceska gynekologie, 2003)
OBJECTIVE: The article presents a review of basic information on incidence and detection of BRCA 1 and BRCA 2 genes mutations. Results of investigation in a group of women with ovarian and breast cancer are presented. DESIGN: Retrospective clinical-laboratory study and review. SETTING: Department of Gynaecology and Obstetrics, 1st Medical Faculty of Charles University, Prague, Apolinárská 18, Czech Republic. MATERIAL AND METHODS: Investigated group consisted of 16 persons--12 patients with ovarian or breast cancer and 4 healthy relatives of a woman--breast cancer patient and a carrier of BRCA 1 gene mutation. Protein truncation test (PTT) was performed in order to detect BRCA 1 gene mutation. This test detects mutations leading to premature termination of protein synthesis. Truncated proteins are easily discriminated from full size. RESULTS: Three BRCA 1 gene alterations were identified in the investigated group of women suffering from ovarian or breast cancer. One asymptomatic person--carrier of BRCA 1 gene mutation--was identified in this study. She was daughter of a woman, a carrier of BRCA 1 gene mutation, with early onset of breast cancer and positive family history. CONCLUSIONS: BRCA 1 and BRCA 2 gene mutations are of particular importance in the increasing risk of ovarian cancer and early onset of breast cancer as well as some other malignancies. Genetic testing and counselling including investigation of some other genetic and environmental factors, related to cancer risk, may be of clinical significance in patients with increased risk of certain malignancies.
Keywords: Breast Neoplasms; Retrospective Studies; Heterozygote; geny BRCA1; Middle Aged; mutace; nádory vaječníků; Adult; Genes, BRCA1; Carcinoma; Genetic Techniques; ženské pohlaví; genetické techniky; Mutation; retrospektivní studie; Humans; lidé středního věku; nádory prsu; dospělí; Female; Ovarian Neoplasms; lidé; karcinom; heterozygot